Considerations in the evaluation and determination of minimal risk in pragmatic clinical trials. (October 2015) - Lantos, John D; Wendler, David; Septimus, Edward; Wahba, Sarita; Madigan, Rosemary; Bliss, Geraldine
Institutional review boards, which are charged with overseeing research, must classify the riskiness of proposed research according to a federal regulation known as the Common Rule (45 CFR 46, Subpart A) and by regulations governing the US Food and Drug Administration codified in 21 CFR 50. If an institutional review board determines that a clinical trial constitutes "minimal risk, " there are important practical implications: the institutional review board may then allow a waiver or alteration of the informed consent process; the study may be carried out in certain vulnerable populations; or the study may be reviewed by institutional review boards using an expedited process. However, it is unclear how institutional review boards should assess the risk levels of pragmatic clinical trials. Such trials typically compare existing, widely used medical therapies or interventions in the setting of routine clinical practice. Some of the therapies may be considered risky of themselves but the study comparing them may or may not add to that pre-existing level of risk. In this article, we examine the common interpretations of research regulations regarding minimal-risk classifications and suggest that they are marked by a high degree of variability and confusion, which in turn may ultimately harm patients by delaying or hindering potentially beneficial research. We advocate for a clear differentiation between the risks associated with a given therapy and the incremental risk incurred during research evaluating those therapies as a basic principle for evaluating the risk of a pragmatic clinical trial. We then examine two pragmatic clinical trials and consider how various factors including clinical equipoise, practice variation, research methods such as cluster randomization, and patients' perspectives may contribute to current and evolving concepts of minimal-risk determinations, and how this understanding in turn affects the design and conduct of pragmatic clinical trials.